Australia [videorecording (DVD)] - Luhrmann, Baz; Kidman, Nicole, 1967-; Jackman, Hugh; Baroo, Eddie, 1968- (20th Century Fox Home Entertainment, 2009)
Australia, 1940s. An English aristocrat inherits a large ranch. English cattle barons plot to take her land and she reluctantly joins forces with a rough-hewn cattle drover to protect her ranch. Together they experience four life-altering years, a love affair and the bombing of Darwin during World War II.